Effect of age on pulmonary embolism - Keller, K.; Beule, J.; Coldewey, M.; Dippold, W.; Balzer, J. O. (Phlebologie, 2014)
Background: Age is an important and independent risk factor for venous thromboembolism (VTE) and pulmonary embolism (PE). The objectives of this study were to investigate the effects of aging process on PE with regard to the severity of PE, symptoms, inhospital death, history of PE, ECG, echocardiographic, and laboratory findings.Methods: 182 patients with confirmed PE were reviewed retrospectively and subdivided into 4 age groups (<60, 60–69, 70–79 and ≥ 80 years). Analysis of patients’ symptoms, history, echocardiographic, electrocardiographic and laboratory parameters was performed.Results: Proportion of women increased with age (<60 years: 41.5 % vs. 80+ years: 73.1 %, P<0.05). Also percentage of right ventricular dysfunction (RVD) was highest in eldest age group (60–69 years: 42.4 % vs. 80+ years: 75 %, P<0.05). Systolic pulmonary artery pressure (sPAP) was significantly higher in the 80+ years age group. The sPAP was constant from the <60 years group (29.0 ± 17.4 mmHg) to the 60–69 years group (27.4 ± 19.3 mmHg), and increased from the 60–69 years and 70–79 years group (33.8 ± 17.5 mmHg) to the 80+ years groups (44.3 ± 14.3 mmHg) (<60 vs. 80+ and 60–69 vs. 80+ years: respectively P<0.001 and 70–79 vs. 80+ years: P<0.05).Regression model for PE patients 80years showed an association between age 80+ and female gender (OR, 2.53; 95%CI: 1.07–5.99, p<0.05), right bundle branch block (OR, 3.07; 95%CI: 1.05–9.02, p<0.05), RVD (OR, 2.53; 95%CI: 1.07–6.00, p<0.05) and sPAP (OR, 1.05; 95%CI: 1.02–1.08, p<0.001). Pearson correlation matrix revealed a significant correlation between age and sPAP (r=0.30, P<0.001).Conclusions: Right ventricular load at acute PE event, evident from RVD and elevated sPAP, increases with age. RVD is connected with higher mortality in PE patients. High sPAP at acute PE event is one of the well-known risk factors for the development of chronic thromboembolic pulmonary hypertension in long-term. Proportion of female PE patients increases with age.
Keywords: Pulmonary embolism; venous thromboembolism; aging; systolic pulmonary artery pressure